Pengaruh Quiet Quitting Terhadap Kinerja Karyawan Generasi Z: Peran Mediasi Work Engagement di Kota Tasikmalaya - Laila Cahyani; Sri Sudiarti (Yayasan Literasi Sains Indonesia, 2026)
Quiet quitting the deliberate restriction of work effort to contractual minimums poses a growing threat to employee performance, particularly among Generation Z in MSMEs characterized by limited HR formalization and multi-tasking demands. This study investigates the effect of quiet quitting on job performance among Generation Z employees in micro, small, and medium enterprises (MSMEs) in Tasikmalaya City, West Java—a region with an open unemployment rate of 6.49% (BPS, 2024) that surpasses the national average, and whose MSME-dominated economy creates conditions where boundary-setting behavior is especially prevalent—with work engagement as a mediating variable. Using a quantitative-explanatory design, data were collected from 97 purposively sampled Gen Z MSME employees (minimum six months’ tenure, ensuring post-adaptation familiarity with organizational work culture) and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). All instruments adapted from English were subjected to back-translation procedures to ensure content validity. Results reveal that quiet quitting has no direct effect on job performance, yet exerts a significant positive effect on work engagement a counterintuitive finding explained through Conservation of Resources Theory. Work engagement, in turn, strongly predicts job performance and fully mediates the quiet quitting performance relationship. These findings challenge prevailing assumptions about quiet quitting as uniformly detrimental, suggesting that boundary-setting behavior may paradoxically sustain employee engagement in MSME settings. Organizations are advised to prioritize engagement-building interventions over punitive responses to quiet quitting.